PENGARUH GAYA MENGAJAR RESIPROKAL DAN KOMANDO TERHADAP KETERAMPILANGULING BELAKANG PADA PEMBELAJARAN SENAM LANTAI SISWA KELAS VII DI SMP NEGERI 1 CIAWI BOGOR - Ingram, Syuhud Ilyasa (2013)
Teaching style from a teacher is a way that used in making connection or interaction with students within the teaching learning process. The good and correct application of teaching style can make the goal of the teaching process achieved. This research conducted to find out how is the influence of two teaching style that will applied to the students, there are reciprocal teaching style and commando teaching style. Which is teaching style that has bigger influence for the students? Research method that used in this research is experiment and the research plan that used is "pre test and post test comparative control". The respondent of the research is 46 students in first grade in Junior High School 1 Ciawi Bogor that choose randomly. The research instrument refers to scoring scale that stated by Schembri (1989:16) with scoring from 1 to 5. Research hypothesis use equity of two average one part (t-test), conclude that influence of commando teaching style is more significant compared to reciprocal teaching style. Suggestion for floor gymnastic teaching process especially for back roll skill as basic movement should use commando teaching style.